Praktik Toleransi Dan Harmonisasi Antar Pemeluk Agama (Studi Fenomenologi Desa Bondo, Jepara) - Normalita, Aulia; Wahab, Abdul; Kafid, Nur (Pascasarjana IAIN Metro, 2025)
The Bondo people practice tolerance through various practices, one of which is Ngejekke. Ngejekke is one of the cultures of the Muslim community of Jepara when a Muslim dies. Uniquely, this tradition is not only followed by Muslims, but also non-Muslims. At the stages of the implementation process, such as the Welcome on behalf of the host (even if they are Muslim) is still represented by a Priest. This study aims to determine the practice of tolerance and harmony between religious adherents and the social context or what factors encourage the practice of tolerance in the Bondo community that is maintained and passed down from generation to generation. The research method uses descriptive qualitative with a process of data retrieval, data clustering, data analysis, and reflection. The approach used is phenomenology by adopting Peter L. Berger's theory of social construction to see how the construction of moderation practices that are part of the life of the Bondo community. The results show that the practice of tolerance and harmony between religious adherents in Bondo village was formed long ago and gave birth to various religious traditions such as interfaith holiday gatherings, sea alms, earth alms, and baratan which involve both. The social context or factors that encourage the practice of tolerance are based on justice and awareness of each individual, support from the government, community leaders, and other policy makers in the local area in maintaining and striving for peace between religious communities.